Algebraic Tangent Cones of Reflexive Sheaves. (6th December 2018) - Chen, Xuemiao; Sun, Song
Abstract: We study the notion of algebraic tangent cones at singularities of reflexive sheaves. These correspond to extensions of reflexive sheaves across a negative divisor. We show the existence of optimal extensions in a constructive manner, and we prove the uniqueness in a suitable sense. The results here are an algebro-geometric counterpart of our previous study on singularities of Hermitian–Yang–Mills connections.